Human Perception of a Haptic Shape-changing Interface with Variable Rigidity and Size - Boem, Alberto; Enzaki, Yuuki; Yano, Hiroaki; Iwata, Hiroo (Proceedings (IEEE Conference on Virtual Reality and 3D User Interfaces. Online), 2019)
This paper studies the characteristics of the human perception of a haptic shape-changing interface, capable of altering its size and rigidity simultaneously for presenting characteristics of virtual objects physically. The haptic interface is composed of an array of computer-controlled balloons, with two mechanisms, one for changing size and one for changing rigidity. We manufactured two balloons and conducted psychophysical experiments with twenty subjects to measure perceived sensory thresholds and haptic perception of the change of size and rigidity. The results show that subjects can correctly discriminate different conditions with an acceptable level of accuracy. Our results also suggest that the proposed system can present an ample range of rigidities and variations of the size in a way that is compatible with the human haptic perception of physical materials. Currently, shape-changing interfaces do not hold a defined position in the current VR / AR research. Our results provide basic knowledge for developing novel types of haptic interfaces that can enhance the haptic perception of virtual objects, allowing rich embodied interactions, and synchronize the virtual and the physical world through computationally-controlled materiality.